2009
DOI: 10.1111/j.1524-475x.2009.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life in hospital inpatients with pressure ulceration: Assessment using generic health‐related quality of life measures

Abstract: The objective of this study was to determine the impact of pressure ulceration on health-related quality of life (HRQoL) and to undertake a pilot study for a future larger study. The study comprised two parts. First, data from a large UK prospective cohort study were analyzed and the HRQoL of 218 people with pressure ulcers was compared with that of 2,289 people without ulcers using the Short Form-36 (SF-36) questionnaire. After adjusting for age, sex, and comorbidities, patients with pressure ulceration had s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
11

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(73 citation statements)
references
References 22 publications
1
61
0
11
Order By: Relevance
“…Overall, the mean number of flaws and poorly reported items per study was 13.9, ranging from 7 to 20. Instances of poor reporting accounted for the majority of these (mean 9.4, range [5][6][7][8][9][10][11][12][13]. Studies had an average of 2.9 minor flaws (range 1-5) and 1.5 major flaws (range 0-3).…”
Section: Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the mean number of flaws and poorly reported items per study was 13.9, ranging from 7 to 20. Instances of poor reporting accounted for the majority of these (mean 9.4, range [5][6][7][8][9][10][11][12][13]. Studies had an average of 2.9 minor flaws (range 1-5) and 1.5 major flaws (range 0-3).…”
Section: Quality Assessmentmentioning
confidence: 99%
“…We had already shown that pressure ulcers had a measurable (negative) impact on quality of life when people with pressure ulcers were compared with others matched for age and comorbidities. 9 Research had also given some insights into the negative impact on patients of leg 10,11 and foot 12 ulceration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The utility scores of hospitalised patients in the same age group and with intact skin was 0.66, from an Australian study by Hawthorne et al [28]. The reduction in quality of life (ie, disutility) from pressure ulcers was 0.29 based on the study by Essex et al [29].…”
Section: Utilitiesmentioning
confidence: 99%
“…Attempts to measure changes in HRQL in people with PUs using quantitative data collection methods (i.e. use of generic PRO instruments to evaluate HRQL in PUs) have had inconsistent results; some findings indicate reductions in HRQL for patients with PUs compared to those without [20,21] while others found no differences in HRQL between people with PUs and controls [22,23].…”
Section: Introductionmentioning
confidence: 99%